Analyzing University Students Ill-Structured Problem Solving Ability in Statistics Subject - Machmud, Muhammad Takwin; Utami, Nurul Mu'tia; Fakhri, M. Miftach; Mayasari, Mayasari (Indonesian Journal of Educational Studies, 2023)
This study has an objective to identification university student ill-structured problem solving skills to solve statistical problem. The study is conducted using mixed method study which is including quantitative and qualitative approach. The study involved 68 university students who enrolled in social statistic subject. The data was collected by using a cognitive test instrument which was administered as pre-test and post-test. The pre-test instrument was constructed as a regular form of test instrument which provides specific instruction for university studentss to solve the test. However, the post-test was constructed based on the criteria of ill-structured problem solving. The result shows that there are difference between pre-test and post-test. The difference can be indicated by comparing the T-value which shows higher value than T-table (10,216 ≥ 1,997). it indicates that the university students have more ability in solving problem with instruction rather than solving the ill-structured problem.